(untitled) (Research, Society and Development, 2021)
Introduction: anxiety disorders can be related to sleep disorders as etiological factors or complications; the purpose of this report was to discuss the case of a patient with Generalized Anxiety Disorder and insomnia, who had an improvement in her anxious symptoms with the treatment of insomnia. Her treatment focus was on quality of sleep. Methodology: This is a 32-year-old woman with poor sleep hygiene habits, who was previously treated and who, although her anxiety symptoms improved, was unable to improve her sleep quality. After an intervention with Cognitive-behavioral Therapy, aimed at the treatment of insomnia, there was an improvement in both sleep quality and anxiety symptoms. Conclusion: This case points to the importance of caring for patients’ sleep habits, even those whose primary complaint is another mental disorder.